Evaluation of Shrink-Swell Soils of Chandrabhaga Valley in Semi-Arid Regions of Central India for Soil Resource Management - Vilas K. Kharche, Prakash R. Kadu (Journal of the Indian Society of Soil Science, 2017)
The present study was undertaken to evaluate the shrink-swell soils of Chandrabhaga valley of central India for various crops. Fourteen typifying pedons representing various landforms were studied. Most of the soils were very high in clay content (31-75%), calcareous in nature, imperfect to moderately drained and very slow to moderate saturated hydraulic conductivity (SHC) (0.01-27.4 mm h-1). Lower values of SHC in some soils were due to higher exchangeable sodium percentage (ESP>5) and/or low Ca2+/Mg2+ ratio (